Asteroid Impact and Deflection Assessment mission. (October 2015) - Cheng, A.F.; Atchison, J.; Kantsiper, B.; Rivkin, A.S.; Stickle, A.; Reed, C.; Galvez, A.; Carnelli, I.; Michel, P.; Ulamec, S.
Abstract: The Asteroid Impact and Deflection Assessment (AIDA) mission will be the first space experiment to demonstrate asteroid impact hazard mitigation by using a kinetic impactor to deflect an asteroid. AIDA is an international cooperation entering Phase A study at NASA and ESA, consisting of two mission elements: the NASA Double Asteroid Redirection Test (DART) mission and the ESA Asteroid Impact Mission (AIM) rendezvous mission. The primary goals of AIDA are (i) to test our ability to perform a spacecraft impact on a potentially hazardous near-Earth asteroid and (ii) to measure and characterize the deflection caused by the impact. The AIDA target will be the binary asteroid (65803) Didymos, with the deflection experiment to occur in October, 2022. The DART impact on the secondary member of the binary at ~6 km/s will alter the binary orbit period, which can be measured by Earth-based observatories. The AIM spacecraft will characterize the asteroid target and monitor results of the impact in situ at Didymos. AIDA will return fundamental new information on the mechanical response and impact cratering process at real asteroid scales, and consequently on the collisional evolution of asteroids with implications for planetary defense, human spaceflight, and near-Earth object science and resource utilization. AIDA will return unique information on an asteroid׳s strength, surface physical properties and internal structure. Supporting Earth-based optical and radar observations, numerical simulation studies and laboratory experiments will be an integral part of AIDA. Highlights: AIDA will be the first space mission to demonstrate asteroid impact hazard mitigation. AIDA will use a kinetic impactor to deflect an asteroid and measure the deflection. AIDA is an international cooperation between ESA and NASA. AIDA will study asteroid strength, surface physical properties and internal structure.